Analisis kinerja ruang dan estetika gedung teknik 2 kampus iii uin malang dalam konteks arsitektur pendidikan - Ningsih, Fitria (Maliki Interdisciplinary Journal, 2025)
This analysis examines the spatial performance and aesthetic appeal of the facade of Building 2, Campus III, UIN Maulana Malik Ibrahim Malang, in the context of educational architecture. Using a descriptive mixed-method approach, data was collected through periodic observations (21–30 April 2025), purposive interviews with project stakeholders, and analysis of shop drawings. The results show that the spatial organisation and zoning on floors 1–2 already support teaching functions, with structured circulation and openings that meet lighting standards (20–29%) and natural ventilation (10–13%). The façade is designed to reduce OTTV with west-east orientation, self-shading, and a combination of ASP, ACP, exposed concrete, and GRC materials. However, implementation in the field shows several deviations related to the quality of physical work: imprecise panel joints, numerous hairline cracks in ceramic and plaster finishes, and uneven façade sealant. Recommendations include strengthening facade installation quality control, improving interior finishing details, and optimising cross ventilation to enhance thermal and acoustic comfort.